Process parameter optimisation of laser clad iron based alloy: predictive models of deposition efficiency, porosity and dilution - Reddy, Liam; Preston, Simon P.; Shipway, P.H.; Davis, C.; Hussain, Tanvir (Elsevier, 2018)
As a candidate coating material for heat-exchanger surfaces in commercial power generation boiler, an amorphous/glass forming Fe-Cr-B alloy NanoSteel SHS 7170 was deposited by a 2 kW fibre laser onto a boiler grade steel substrate (15Mo3). A comprehensive trial with 28 single track optimisation runs was carried out to develop models of the influence of three processing parameters, laser power, laser traverse speed and powder feed rate, on powder deposition efficiency, dilution and porosity. It was found that deposition efficiency is dependent on laser power and powder feed rate, increasing with increasing power and decreasing powder feed rate when tested within the parameter window of laser power ranging from 0.4 to 2 kW; traverse speed varying from 150 to 1200 mm min‑1; and powder feed rate varying from 4 to 10 g min‑1. Similarly, it was found that dilution is also dependent on laser power and powder feed rate. Dilution increases with increasing power and decreases with increasing powder feed rate within the same parameter window discussed above. This means that through processing parameter selection, these properties can be adjusted to suit their application. Porosity was found to be independent of processing parameters and instead mostly dependent on the feedstock material. A model was produced for predicting porosity within a powder feedstock, found to be 8.5%. These models were used to successfully produce an optimised coating.